Indonesia's Digital Access Disparities: A Comparative Study of World Bank Data and ASEAN Regional Trends - Eka Nur Aini; Yatimin Yatimin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia's digital transformation faces a unique paradox amid the wave of the 4.0 industrial revolution, where the acceleration of technology adoption has the potential to deepen existing social inequalities. This research was born out of the urgency to understand the dynamics of digital access disparities, which not only have an impact on economic aspects but also affect the equality of community participation in the national digital ecosystem. The objective of this study is to map the evolution of Indonesia's digital divide during the period 2010-2023 while analysing its competitive position in the ASEAN regional context. The method applied integrates a quantitative approach through secondary data analysis from the World Bank and ILO, processed using the Google Colab platform, complemented by interactive visualizations to explore hidden patterns and trends. Research findings reveal a complex story behind Indonesia's optimism about digital transformation. On the one hand, internet user growth shows significant progress at a rate of 11.8% per year, but on the other hand, the digital literacy gap remains at 11.2%. Indonesia's position in fifth place in the ASEAN digital divide map indicates the need for a more focused strategy to catch up with neighbouring countries such as Malaysia and Singapore. Projections of the gap until 2028 show that without appropriate policy intervention, this disparity has the potential to affect national competitiveness in the long term. For future research, it is necessary to expand the scope of analysis to the regional level and integrate qualitative data to understand the deeper root causes of the problem, so that more targeted and contextual policy recommendations can be formulated.